Operations against enemy leaders - Hosmer, Stephen T. (Monographs / reports (Rand Corporation) ;, 2001)
An examination of a number of leadership attacks from World War II to the 21st century. It offers insights into the comparative efficacy of various forms of leadership attacks, their potential coercive and deterrent value, and the possible unintended consequences of their ill-considered use.